Gender Diversity, Recognition and Citizenship - Hines, S. author. aut Link
IX, 150 p.
Keywords: This book examines the meanings and significance of the UK Gender Recognition Act within the context of broader social, cultural, legal, political, theoretical and policy shifts concerning gender and sexual diversity, and addresses current debates about equality and diversity, citizenship and recognition across a range of disciplines.